Metastasis on Chip: Modelling Invasive Breast Cancer Cells - Sharko Gandabura, Vira; Perisé, Ismael; Morato, Laura; Antón, Antonio; Solanas, Estela; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2023)
The purpose of this work is to employ a three-dimensional model to examine breast cancer metastasis from various perspectives. Using a solid breast tumor model exposed to a standard chemotherapeutic treatment scheme, we aim to replicate the earliest stages of the metastatic cascade, focusing on the drug's effect on invasive cells.